Determining the Primary Sources of Uncertainty in Retrieval of Marine Remote Sensing Reflectance From Satellite Ocean Color Sensors - Gilerson, Alexander; Herrera-Estrella, Eder; Foster, Robert; Agagliate, Jacopo; Hu, Chuanmin; Ibrahim, Amir; Franz, Bryan (Frontiers in Remote Sensing, 2022)
Uncertainties in the retrieval of remote sensing reflectance, Rrs, from Ocean Color (OC) satellite sensors have a strong impact on the performance of algorithms for the estimation of chlorophyll-a, mineral concentrations, and inherent optical properties (IOPs). The uncertainties are highest in the blue bands. The total radiance measured at the top of the atmosphere captures the instantaneous state of the atmosphere-ocean system: the in-water conditions, sky and Sun glint reflected from the wind-roughened ocean surface, as well as light scattered from molecules and aerosols in the atmosphere. Each of these components have associated uncertainties, and when combined with the additional uncertainties from instrument noise and the atmospheric correction process they contribute to the total uncertainty budget for the retrieved Rrs. We analyze the contribution of each component uncertainties to the total Rrs uncertainties in SNPP-VIIRS level 2 products, taking advantage of the spectral differences between the components. We examine multiple scenes in the open ocean and coastal waters at spatial resolutions ranging from 2250 to 5250 meters by comparing the retrieved Rrs to in-situ measurements made at several AERONET-OC sites and at the MOBY site. It is shown that uncertainties associated with the molecular (Rayleigh) scattering play the most significant role, while the contributions of other components are usually smaller. Uncertainties in Rayleigh scattering are primarily attributed to the variability of Rayleigh optical thickness (ROT) with a standard deviation of approximately 1.5% of ROT, which can largely explain the frequency of negative Rrs retrievals as observed using the current standard atmospheric correction process employed by NASA. Variability of the sky light reflected from the ocean surface in some conditions also contributed to uncertainties in the blue and to water variability proportional to Rrs, with a very pronounced peak in the green at coastal sites.